Philosophizing as the Way to Approach Death - Jankauskas, Skirmantas (Problemos, 2004)
The paper deals with the introductory part of Plato‘s “Phaedo”, where philosophizing is represented as the way to approach death. Two situations are paralleled – that of the tragedy of Oedipus and that of Socrates waiting for his penalty of death. It is shown that both are dramatized by the premise of freedom that on its turn is supposed by knowledge. Then two ways to resolve the conflict between freedom and destiny are discussed. The paper reveals that the Greek tragedy just states the conflict and finds solution in the negation of one of the conflicting sides, namely, in the negation of knowledge. Greek philosophy in its turn looks for a positive solution of the conflict by the way of subordinating knowledge to destiny. This concern of the Greek philosophy is reflected by the idea of philosophizing as the way to approach death. It is shown that because of his anonymity Greek philosopher cannot privatize the content of his thinking. That is why he can only be a passive spectator of the conflict between the two different kinds of thinking, that of everyday life thinking and philosophizing. Though advocating one approach but at the same time unable to distance from the other because of his anonymity, he realizes his engagement with philosophy with a sense of tragedy. Greek philosopher is forced to renounce the everyday thinking as well as his body that he associates with this kind of thinking. Consequently, for the sake of philosophy, he is forced to deny the life in which and for which he philosophizes. However, death marks the boundary of everyday life, and the orientation towards it makes this kind of life and its values meaningless, thus creating a condition for the anonymous Greek philosopher to engage himself with other – ethical – values and with the other kind of thinking, that is constituted by these values. i.e., with philosophizing.